Consequences of Elitist Reconciliation in Zimbabwe and South Africa: A Comparative Study - Simura, Blessing; Mudimu, George T. (Kamala-Raj Enterprises, 2021)
This paper analyses the reconciliation paths that were taken by Zimbabwe and South Africa after their independence and majority rule struggles. The paper notes that the histories of Zimbabwe and South Africa are similar to each other in some ways: they were both colonized and have similar policies regarding their postindependence political and economic structures. It, however, notes that the post-independence settlements were elitist and alienated the ordinary people who fuelled the struggles, creating a socio-economic and political time bomb that exploded in Zimbabwe and is now threatening to explode in South Africa. The paper uses interviews and documentary research as primary tools for data gathering and is guided by the concept of the ‘Appeasement of Avenging Spirits’ in Zimbabwean indigenous culture.